Clinicopathological and genetic features of Zinner’s syndrome: two case reports and review of the literature - Dai, Ruijie; Jiang, Fan; Fan, Junjie; He, Dalin; Li, Lei; Wu, Kaijie (Frontiers in Urology, 2023)
Zinner's syndrome (ZS) is a rare congenital malformation due to abnormal development of the urogenital tract. It is characterized by the triad of unilateral renal agenesis, ipsilateral seminal vesicle cyst and ipsilateral ejaculatory duct obstruction.Cases are rarely reported in China since the incidence of the disease is low. Symptoms also vary widely among patients and its etiology is unclear. In this article, we described two patients with totally different cinicopathological and genetic features based on exon sequencing.